When new technology joins old documents and east meets west: virtually reconstructing the Fisher Island Pagoda Lighthouse (China) - Anthony K.H. Leung; Stephen Davies; Steve H. Ching (Virtual Archaeology Review)
Located on the route between Xiamen and Taiwan (China), the Penghu (Pescadores Islands) are an archipelago and the site of a military garrison. The second largest island, Xiyu or Fisher Island, was accordingly an obvious point to build a navigational marker to guide sailors. Records indicate that some type of a marker, in the form of a tower or pagoda, was constructed in the 17thcentury. However, in 1778the original was replaced by a different sort of pagoda tower. The new structure has long been known to have been a purpose fully designed lighthouse. Although today’s Yuwengdao lighthouse, built in 1875, has become a famous heritage landmark, the earlier 1778 structure, it can be argued has greater heritage significance in that it was an entirely original creation preceding the introduction of western lighthouse technology in China by nearly a century. Thanks to the fortunate discovery of a hitherto unknown photograph of this earlier lighthouse backed by further research in early navigational documents, gazetteers, charts and inscriptions and The authors have been able to make a 3D virtual reconstruction using state-of-the-art Revit software and thus answer several research questions about this old lighthouse pagoda, including dimensions, location, orientation, function and materials.